Molecular surveillance of putative drug resistance markers of antifolate and artemisinin among imported Plasmodium falciparum in Qatar. (19th May 2019) - Bansal, Devendra; Bharti, Praveen K.; Acharya, Anushree; Abdelraheem, Mohamed H; Patel, Priyanka; Elmalik, Ashraf; Abosalah, Salem; Khan, Fahmi Y.; ElKhalifa, Mohamed; Kaur, Hargobinder; Farag, Elmoubasher; Sarmah, Nilanju P; et al.
ABSTRACT: Malaria remains a significant public health challenge and is of global importance. Imported malaria is a growing problem in non-endemic areas throughout the world and also in Qatar due to a massive influx of migrants from endemic countries. Antimalarial drug resistance is an important deterrent in our fight against malaria today. Molecular markers mirror intrinsic antimalarial drug resistance and their changes precede clinical resistance. Thus, in the present study, molecular markers of sulphadoxine-pyrimethamine ( Pfdhfr and Pfdhps ) and artemisinin ( PfATPase6 and Pfk13 ) were sequenced to determine the drug resistance genotypes among 118 imported P. falciparum isolates in Qatar, between 2013 and 2016. All the isolates had mutant Pfdhfr alleles, with either double mutant (51I/108N) (59.3%) or triple mutant (51I, 59R and 108N) (30.6%) genotypes. I164L substitution was not found in this study. In case of Pfdhps, majority of the samples were carriers of either single (S436A/ A437G/ K540E) mutant (47.2%) or double (S436A/K540E, A437G/K540E, K540E/A581G) mutant (39.8%). A single novel point mutation (431V) was observed in the samples originated from Nigeria and Ghana. Polymorphisms in PfATPase6 were absent and only one non-synonymous mutation in Pfk13 was found at codon G453A from a sample of Kenyan origin. High levels of sulphadoxine-pyrimethamine resistance in the present study provide potential information about the spread of antimalarial drug resistance and will be beneficial for the treatment of imported malaria cases in Qatar.